Adhesive Dynamics Simulations of the Shear Threshold Effect for Leukocytes - Caputo, Kelly E. (Biophysical Society, 2007)
Many experiments have measured the effect of force on the dissociation of single selectin bonds, but it is not yet clear how the force dependence of molecular dissociation can influence the rolling of cells expressing selectin molecules. Recent experiments using constant-force atomic force microscopy or high-resolution microscopic observations of pause-time distributions of cells in a flow chamber show that for some bonds, the dissociation rate is high at low force and initially decreases with force, indicating a catch bond. As the force continues to increase, the dissociation rate increases again, like a slip bond. It has been proposed that this catch-slip bond leads to the shear threshold effect, in which a certain level of shear rate is required to achieve rolling. We have incorporated a catch-slip dissociation rate into adhesive dynamics simulations of cell rolling. Using a relatively simple model for the shear-controlled association rate for selectin bonds, we were able to recreate characteristics of the shear threshold effect seen most prominently for rolling through L-selectin. The rolling velocity as a function of shear rate showed a minimum near 100 s(−1). Furthermore, cells were observed to roll at a shear rate near the threshold, but detach and move more quickly when the shear rate was dropped below the threshold. Finally, using adhesive dynamics, we were able to determine ranges of parameters necessary to see the shear threshold effect in the rolling velocity. In summary, we found through simulation that the catch-slip behavior of selectin bonds can be responsible for the shear threshold effect.